(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to evaluate the effectiveness of clove, cumin, and cumin oils against the fungus Rhizoctonia solani, which causes seedling drop disease in tomato, in the culture medium and under field conditions, and compare it with the effectiveness of the fungicide Rhizolex. 500, 1000 ppm inhibition of fungus growth by 79.56, 100, 100% for clove oil, 44.40, 47.20, 70.30 for cumin oil, and 40.13, 40.13, 51.83% for the three concentrations, respectively. The fungus caused a high decrease in the percentage of germination, amounting to 20% compared to 100% in comparison, accompanied by a similar decrease in plant height